2009
DOI: 10.1002/syn.20688
|View full text |Cite
|
Sign up to set email alerts
|

GABAA‐benzodiazepine receptor availability in smokers and nonsmokers: Relationship to subsyndromal anxiety and depression

Abstract: Many smokers experience subsyndromal anxiety symptoms while smoking and during acute abstinence, which may contribute to relapse. We hypothesized that cortical gamma aminobutiric acid A – benzodiazepine receptor (GABAA-BZR) availability in smokers and nonsmokers might be related to the expression of subsyndromal anxiety, depressive, and pain symptoms. Cortical GABAA-BZRs were imaged in 15 smokers (8 men; 7 women), and 15 healthy age and sex-matched nonsmokers, and 4 abstinent tobacco smokers (3 men; 1 woman) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 61 publications
2
15
0
Order By: Relevance
“…However, a preliminary study conducted in our laboratory did not reveal a significant effect of tobacco smoking on the GABA A -BZR availability. Specifically, we did not detect significant differences in GABA A -BZR availability in living human tobacco smokers compared to nonsmokers, nor did we observe a difference in GABA A -BZR availability from baseline to abstinence in a small subset of smokers who agreed to abstain from smoking for 5 weeks and repeated the scanning protocol (Esterlis et al, 2009). The difference observed between the above mentioned rodent study and our human study may be due to a sex-specific regulation of GABA levels by sex-steroid hormones, which in nonsmoking women are highest during the follicular phase and lowest in the luteal phase (Epperson et al, 2002).…”
Section: Introductionmentioning
confidence: 73%
“…However, a preliminary study conducted in our laboratory did not reveal a significant effect of tobacco smoking on the GABA A -BZR availability. Specifically, we did not detect significant differences in GABA A -BZR availability in living human tobacco smokers compared to nonsmokers, nor did we observe a difference in GABA A -BZR availability from baseline to abstinence in a small subset of smokers who agreed to abstain from smoking for 5 weeks and repeated the scanning protocol (Esterlis et al, 2009). The difference observed between the above mentioned rodent study and our human study may be due to a sex-specific regulation of GABA levels by sex-steroid hormones, which in nonsmoking women are highest during the follicular phase and lowest in the luteal phase (Epperson et al, 2002).…”
Section: Introductionmentioning
confidence: 73%
“…However, evidence from neuroimaging studies using non‐specific benzodiazepine radiotracers [ 11 C]flumazenil PET or [ 123 I]iomazenil SPET about GABA A receptor availability within the amygdala in relation to these processes is limited and inconsistent. The most evidence relates to anxiety where no relationship or negative correlations have been reported in HV and both positive and negative correlations in patients with anxiety disorders (Abadie et al 1999; Esterlis et al 2009; Hasler et al 2008; Lingford‐Hughes et al 1998). …”
Section: Discussionmentioning
confidence: 99%
“…The effects of chronic nicotine administration on GABA activity are less clear. While a preclinical study indicated chronic nicotine treatment increased the density of BZ receptors in the cerebral cortex (Magata et al, 2000), a recent neuroimaging study in our laboratory demonstrated no difference in GABA A -BZR availability between current healthy smokers and nonsmokers (Esterlis et al, 2009). An important caveat to this study is that smokers were imaged at 7 hours of smoking abstinence.…”
Section: Effects Of Nicotine On Gabaa Receptorsmentioning
confidence: 89%